Krulik and Rudnik Model Heuristic Strategy in Mathematics Problem Solving - Kusdinar, Uus; Sukestiyarno, Sukestiyarno; Isnarto, Isnarto; Istiandaru, Afit (International Journal on Emerging Mathematics Education, 2017)
Heuristic strategy is one of the mathematics problem solving strategies to gain effective results. This research aimed to analyze the use of the heuristic strategies based on the modification of the Krulik and Rudnik model. This research discovered and classified the studentsâ heuristic strategies which can be used as a basis to provide assistance in the learning. This research was a qualitative research involving 32 students of SMP Muhammadiyah 4 Yogyakarta as its subjects. The research variables are the indicators of the Krulik and Rudnik heuristic models which the students performed including: read and think, explore and plan, select a strategy, find and answer, as well as reflect and extend. The data was taken through questionnaire and interview methods. The result suggested that: 2 students (6.25%) were in the good category as they did all of the heuristic strategies more often; 21 students (65.62%) were in the fair category since they implemented some indicators of the heuristic strategies; and 9 students (28.13%) were in the poor category since they were lack in implementing the heuristic strategies. In all categories, indicator of find and answer was more oftenly done by the students while the indicator of explore and plan was less done.